2021
DOI: 10.3390/su132112020
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Contents and Assessment of Soil Contamination in Different Land-Use Types in the Qaidam Basin

Abstract: Due to the unique geographical location and rapid development in the agricultural industry, heavy metals’ risk of soil contamination in the Qaidam Basin is gradually increasing. The following study was conducted to determine the soil heavy metal contents under different types of land use, contamination levels, and the physicochemical properties of soil. Soil samples were collected from facility lands, orchards, farmlands, and grasslands at 0–10 and 10–20 cm soil layers. Heavy metals including copper (Cu), chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The bioavailability of HMs could be increased with the relatively high soil TP and TN concentrations (Xiao et al, 2016). Considering the roadside soil TP and TN usually comes from fertilizers and traffic emissions (Singh et al, 2018), the correlations in terms of TN and TP demonstrated the influence of anthropogenic activities on HM concentrations in soils (Martin & Kaplan, 1998; Nuralykyzy et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The bioavailability of HMs could be increased with the relatively high soil TP and TN concentrations (Xiao et al, 2016). Considering the roadside soil TP and TN usually comes from fertilizers and traffic emissions (Singh et al, 2018), the correlations in terms of TN and TP demonstrated the influence of anthropogenic activities on HM concentrations in soils (Martin & Kaplan, 1998; Nuralykyzy et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The soil is a non-renewable natural resource that provides various critical ecosystem functions, including supporting the growth of crops and the distribution of water and gases in the environment. It also serves as a buffer in the control of organic and inorganic substances [4,5] . Globally, heavy metal pollution of soil has attracted growing attention [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Various elements, including the type of plastic, species of heavy metal, properties of soil, and the environment, might affect the unique interactions between heavy metals and plastic-contaminated soil [4], [13]. Heavy metals including Cadmium (Cd), Copper (Cu), Lead (Pb) and Zinc (Zn) are most commonly found in the contaminated soil [1], [2], [16]. This type of pollution persisting for a long time in the soil environment, is medically dangerous, and is widely spread.…”
Section: Introductionmentioning
confidence: 99%